PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SMK MELALUI PENDEKATAN MATEMATIKA REALISTIK - Muhammad Ridha; Marwan Marwan; B. I. Ansari (Jurnal Peluang, 2019)
Mathematically critical thinking skills are two very important capabilities owned by a student. It allows the students to reason and solve problems in everyday life. The ability to cultivate, then one relevant learning is realistic mathematics learning. This study aims to analyze the increasa in critical thinking skills students acquire mathematical learning of mathematics using realistic mathematics approach whit student who received conventional mathematics, as well as see the interaction by the level of prior knowledge of students. This study is a quasi experimental study research design Pretest Posttest Control Design. The population of this research is all class X students at SMK Negeri 1 Meulaboh by taking two classes of samples taken at random from the 7 classes available. Data analysis was performed using t-test and ANOVA two lanes with a significance level of 0.05, both based on the whole student or based on prior knowledge of students. Based on the results of the study concluded that: 1) peningkatan critical thinking skills mathematical students taught through realistic mathematics approach is better than the critical thinking skills of students taught by conventional, 2) terdapat interaction between realistic mathematics approach to the level of students' critical thinking skills mathematically.